Living on the lake in prehistoric Europe : 150 years of lake-dwelling research - Menotti, Francesco (Taylor & Francis e-Library, 2004)
The chance discovery in 1854 of a prehistoric lake village on Lake Zurich triggered what we now call the - 'lake-dwelling phenomenon'. One hundred and fifty years of research and animated academic disputes have transformed the phenomenon into one of the most reliable sources of information in wetland archaeology. This definitive volume provides an overview of the development of lake village studies, explores the impact of a range of scientific techniques on the settlements and considers how the public can relate to this evocative and exciting branch of archaeology. It explains how the multidisciplinary research context has significantly improved our knowledge of prehistoric wetland communities, from an environmental as well as a cultural perspective.